1998
DOI: 10.1073/pnas.95.19.11471
|View full text |Cite
|
Sign up to set email alerts
|

One face of a transmembrane helix is crucial in mechanosensitive channel gating

Abstract: MscL is a mechanosensitive channel in bacteria that responds directly to membrane tension by opening a large conductance pore. To determine functionally important residues within this molecule, we have randomly mutagenized mscL, expressed the genes in living bacteria, and screened for gain-of-function mutants with hampered growth. Expression of these genes caused leakage of cytoplasmic solutes on little or no hypo-osmotic stress. In excised patches, the mutant channels gated at membrane tensions that are less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
277
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 188 publications
(306 citation statements)
references
References 29 publications
27
277
2
Order By: Relevance
“…Thus, we focus on subtler changes that cause the channel to tend toward opening. Such rare mutations have been recovered from screens in Escherichia coli for a mechanosensitive channel (24) or in yeast for native (25) and foreign K ϩ channel (26) after single-gene mutagenesis. Among TRP channels, disease or experimental point mutations reported to date all seem to cause reduction or loss of channel activities, including the dominant polycystic kidney disease (PKD) alleles (27) and a dominant-negative construct of TrpV1 (28).…”
Section: Molecular Activities Of Y458h Y473hmentioning
confidence: 99%
“…Thus, we focus on subtler changes that cause the channel to tend toward opening. Such rare mutations have been recovered from screens in Escherichia coli for a mechanosensitive channel (24) or in yeast for native (25) and foreign K ϩ channel (26) after single-gene mutagenesis. Among TRP channels, disease or experimental point mutations reported to date all seem to cause reduction or loss of channel activities, including the dominant polycystic kidney disease (PKD) alleles (27) and a dominant-negative construct of TrpV1 (28).…”
Section: Molecular Activities Of Y458h Y473hmentioning
confidence: 99%
“…It has been suggested that a Gly residue and its adjacent amino acid residues in the gate play important roles in the gating mechanism in several ion channels. For example, the most conserved Gly 22 residue of E. coli MscL functions as the gate (40,41). When Gly 22 is replaced with hydrophilic residues, the resulting mutant MscL channels become more mechanosensitive.…”
Section: Important Amino Acid Residues In H3mentioning
confidence: 99%
“…12 Many studies have been performed using site-directed mutagenesis in order to better understand the structure-function of MscL. [13][14][15][16][17][18][19] One of these studies produced an estimation of the tension-sensing site in MscL using random scanning mutagenesis, where individual hydrophobic AAs facing the lipids were replaced with the hydrophilic AA asparagine to identify any "loss-of-function" mutants lacking mechanosensitivity. 15 As the result, it was found that replacement of one of seven amino residues located at the periplasmic end of the transmembrane helices caused the loss of MscL mechanosensitivity, suggesting that one or some of them may act as a tension sensor in MscL.…”
Section: Introductionmentioning
confidence: 99%